KEDUDUKAN HUKUM ADAT DAYAK BENUAQ BERKAITAN KASUS ASUSILA DI KABUPATEN KUTAI BARAT DI TINJAU DARI HUKUM POSITIF - DONNI CHANDRA (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Provincial Regulation of East Kalimantan on guidelines for recognition and protection of indigenous and tribal peoples in East Kalimantan province. To implement the recognition and protection of indigenous and tribal peoples in the Province of East Kalimantan which is a reflection of the diversity of the Indonesian nation that must be recognized and protected in accordance with the 1945 Constitution of the State of the Republic, it is necessary to stipulate local regulations on the recognition and protection of indigenous and tribal peoples in Kalimantan East.The basic law of this regional regulation is: Article 18 paragraph (6) of the 1945 Constitution; Law No.25 of 1956; UU no. 41 of 1999; UU no. 12 Year 2011; UU no. 6 Year 2014; PP no. 43 Year 2014 PERMENDAGRI No. 1 Year 2014; PERMENDAGRI No. 52 of 2014. In this regulation, the guidelines for the recognition and protection of indigenous and tribal peoples and their details are covered.This law comes into effect on the date of promulgation, 1 September 2015. This regulation explains the status of indigenous and tribal peoples, the rights and obligations of indigenous and tribal peoples, provincial authorities, committee establishment, recognition and protection mechanisms, guidance and supervision and judicial provisions. Keywords: Dayak Benuaq Customary Law, Asusila, and Positive Law.ABSTRACT Provincial Regulation of East Kalimantan on guidelines for recognition and protection of indigenous and tribal peoples in East Kalimantan province. To implement the recognition and protection of indigenous and tribal peoples in the Province of East Kalimantan which is a reflection of the diversity of the Indonesian nation that must be recognized and protected in accordance with the 1945 Constitution of the State of the Republic, it is necessary to stipulate local regulations on the recognition and protection of indigenous and tribal peoples in Kalimantan East.The basic law of this regional regulation is: Article 18 paragraph (6) of the 1945 Constitution; Law No.25 of 1956; UU no. 41 of 1999; UU no. 12 Year 2011; UU no. 6 Year 2014; PP no. 43 Year 2014 PERMENDAGRI No. 1 Year 2014; PERMENDAGRI No. 52 of 2014. In this regulation, the guidelines for the recognition and protection of indigenous and tribal peoples and their details are covered.This law comes into effect on the date of promulgation, 1 September 2015. This regulation explains the status of indigenous and tribal peoples, the rights and obligations of indigenous and tribal peoples, provincial authorities, committee establishment, recognition and protection mechanisms, guidance and supervision and judicial provisions. Keywords: Dayak Benuaq Customary Law, Asusila, and Positive Law.